The role of technology in creating modern trends in accounting and auditing (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Accounting has evolved to keep pace with the latest economic, political, social and technological developments. Therefore, researchers are also needed to include in their research agenda emerging topics in the field of accounting. This research selects technological questions in accounting as a research topic, reviewing literature that uses archival research as a method and content analysis as a method. Using different tools to evaluate qualitative data, this content analysis provides a summary of those papers, such as their main topics, most popular words, and cluster analysis. One of the leading journals, the International Journal of Accounting Information Systems, has been used as a source of information due to its scope linking accounting and technological issues. Data from 2000 to 2022 have been selected to provide evaluative analysis since the beginning of this century, with a particular focus on the recent period.